Data Air: Business Data Analytics based on Airline Data - Shankar et al., Venkatesh Gauri (International Journal of Advanced Science and Technology, 2020)
In highly advancing and flourishing world of technology, delivering quick and efficient solutions for every day to day work of a common user is the increasing need of today. It becomes highly essential to get the things right at first place. Flight defers cause a great deal of burden to travellers. It could make them late to their booked occasions or miss a corresponding flight, accordingly prompting outrage and disappointment. Likewise, travellers may not generally be qualified for pay when a postponement happens. A flight is said to be postponed when it shows up at least 15 minutes after the fact than the calendar. Carriers guarantee that couple of the explanations behind flight delays are aircraft glitches, climate conditions, support issues with the airplane, blockage in air traffic, late appearance of the airplane to be utilized for the departure from a past flight and security issues. The main objective of this paper is to perform analysis on the data of the year 2014,2015,2016 and provide actionable itinerary for the travellers on what are the best airports, flights, time for travel in the next year. This paper targets examining, cleaning, changing, and displaying information which may comprise of either verifiable records or new data that has been prepared for continuous investigation employments. This is a push to portray, anticipate, and improve business execution. These bits of knowledge from information are utilized to prescribe activity or to manage dynamic established in business setting. Data analytics initiatives can help businesses improve in various ways like increasing revenues, improve operational efficiency, etc. thereby gaining a competitive edge over rivals. Hence, data analytics combined with visualization is playing a vital role in today’s corporate world.